Proposal of a Strategic Endomarketing Model for Leadership and Optimization of Results in Human Talent Management (Revista Científica Interdisciplinaria Investigación y Saberes, 2025)
Organizational evolution forces top executives to redirect strategies related to human resources, especially in the processes of innovation, design and implementation of tactics that generate differentiation from their competitors. This article aims to address the problem, which determines the context of the tacit and implicit obligations that every organization assumes towards its collaborators, under the universal parameters established in the legal and contextual framework of the Honduran financial system, the objectives to be achieved, as well as presenting a proposed model applicable in the light of modern organizational needs, as a scientific contribution that complements the best practices existing in the reference sector.